GOVERNMENT INTERVENTION AND GROWTH OF AGRICULTURAL SECTOR IN NIGERIA - Ibeaja, Uzoma F.; Amadi, Kevin T.; Dim, Henry C. (African Journal of Social and Behavioural Sciences, 2022)
This study examined government intervention and growth of the agricultural sector in Nigeria from 1986 – 2020. The government intervention policies were represented by government budgetary allocations to the various agricultural development programmes for the period studied, which were constrained by corruption, tribalism, lack of funds, mismanagement of funds, political instability among others. In addition, specialized banks loans to the agricultural sector and interest rate on agricultural loans were the other explanatory variables. The dependent variable was agricultural sector’s output. The data were sourced from CBN Statistical Bulletin and Bank of Agriculture Publications for various years which were analyzed using the Autoregressive Distributed Lag (ARDL) model. The findings derived from the tested hypothesis of this research revealed that government intervention decreased agricultural output but not significantly in the long run, while specialized banks’ loans increased agricultural output significantly in the long run. Also, interest rate on agricultural loans increased agricultural output but not significantly. The short run speed of adjustment of the model was estimated at 11.3%. The study concluded that government intervention has come in the form of various agricultural development programmes but it appears that the funding of these programmes has not increased output of the agricultural sector due to insufficiency of the funding or the funds not reaching the intended farmers. Specialized banks have shown more effective energy in growing the agricultural sector with a positive and significant coefficient. The study recommended that accountability, transparency and judicious disbursement of agricultural intervention funds need to be enshrined in addition to increased funding of the agricultural sector by specialized banks.